2018
DOI: 10.3390/cancers10100370
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental pH and Exosome Levels Interplay in Human Cancer Cell Lines of Different Histotypes

Abstract: Exosomes are extracellular nanovesicles primarily involved in the pathogenesis of many diseases including cancer. This study was set out from recent evidence that extracellular acidity may increase the exosome release by cancer cells. However, this preliminary evidence did not provide solid information on whether the pH-dependent exosome over-release represents a common feature of all cancers. To the purpose of demonstrating that cancer acidity is a major determinant in inducing an increased exosome release by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 44 publications
(83 reference statements)
6
144
0
Order By: Relevance
“…[44] In this study, we followed recommended MISEV 2018 guidelines to characterize the isolated serum small vesicles. [50] Alternate method, nanoscale flow cytometry, could also generate both the size and EVs markers expression in gated subpopulations. [46] A subset of samples used for validation was used for isolating small EVs using ultracentrifugation sucrose density gradient method.…”
Section: Discussionmentioning
confidence: 99%
“…[44] In this study, we followed recommended MISEV 2018 guidelines to characterize the isolated serum small vesicles. [50] Alternate method, nanoscale flow cytometry, could also generate both the size and EVs markers expression in gated subpopulations. [46] A subset of samples used for validation was used for isolating small EVs using ultracentrifugation sucrose density gradient method.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our groups showed that the tumour acidic microenvironment markedly increases the number of exosomes, also those expressing CA IX 16,17,30 . However, never the acidity of the tumour microenvironment has been associated with the intraluminal acidification of the exosome released by cancer cells.…”
Section: Exosomes From Pca Plasma Patients Are Acidicmentioning
confidence: 99%
“…Therefore, tumour cells up-regulate proton exchangers and transporters throwing out excess protons through Vacuolar ATPase (V-ATPase), Naþ/H þ exchanger (NHE), monocarboxylate transporters (MCTs), cotransporter sodium bicarbonate (NBC), and carbonic anhydrase 9 (CA IX) 2,[11][12][13] . Chemoresistance of cancers and the increase in exosome release are two well-known effects of the extracellular acidification [14][15][16][17][18] . Exosomes are extracellular nanovesicles of 40-180 nm secreted by all cells and capable of modulating physiological or pathological processes, including tumour progression, through transmitting into target cells their cargo (lipids, proteins, DNA, mRNA or microRNA) [18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we cultured cells of the human breast cancer cell line MDA-MB-231, both at a standard pH of 7.5 and at a low, slightly acidic pH of 6.5, which is representative of average tumor acidity. 39 We fluorescently labeled magnetosomes with and without expression of pHLIP using a lipophilic membrane dye (DiI) inserted into the membrane of the magnetosome. We incubated both wild-type and pHLIP-functionalized magnetosomes with MDA-MB-231 cells at low pH and standard pH and analyzed the binding efficiency by flow cytometry.…”
Section: Peptide-fused Magnetosomes Serve As Functional Binding Agentsmentioning
confidence: 99%